Human Herpesviruses 6A and 6B in Reproductive Diseases - Komaroff, Anthony L.; Rizzo, Roberta; Ecker, Jeffrey L. (Frontiers in Immunology, 2021)
Human herpesviruses 6A (HHV-6A) and human herpesvirus 6B (HHV-6B)—collectively, HHV-6A/B—are recently-discovered but ancient human viruses. The vast majority of people acquire one or both viruses, typically very early in life, producing an ineradicable lifelong infection. The viruses have been linked to several neurological, pulmonary and hematological diseases. In early human history, the viruses on multiple occasions infected a germ cell, and integrated their DNA into a human chromosome. As a result, about 1% of humans are born with the full viral genome present in every cell, with uncertain consequences for health. HHV-6A may play a role in 43% of cases of primary unexplained infertility. Both the inherited and acquired viruses may occasionally trigger several of the factors that are important in the pathogenesis of preeclampsia. Transplacental infection occurs in 1-2% of pregnancies, with some evidence suggesting adverse health consequences for the child. While emerging knowledge about these viruses in reproductive diseases is not sufficient to suggest any changes in current practice, we write this review to indicate the need for further research that could prove practice-changing.